Firearm Violence, Access to Care, and Gentrification: A Moving Target for American Trauma Systems. Issue 2 (August 2021) - Scantling, Dane; Orji, Whitney; Hatchimonji, Justin; Kaufman, Elinore; Holena, Daniel
Abstract : Objective: We aimed to determine whether gentrification predicts the movement of shooting victims over time and if this process has decreased access to care. Background: Trauma centers remain fixed in space, but the populations they serve do not. Nationally, gentrification has displaced disadvantaged communities most at risk for violent injury, potentially decreasing access to care. This process has not been studied, but an increase of only 1 mile from a trauma center increases shooting mortality up to 22%. Methods: We performed a cross-sectional study utilizing Philadelphia Police Department (PPD) and Pennsylvania trauma systems outcome (PTOS) data 2006–2018. Shootings were mapped and grouped into census tracts. They were then cross-mapped with gentrification data and hospital location. PPD and PTOS shooting data were compared to ensure patients requiring trauma care were captured. Census tracts with ≥500 residents with income and median home values in the bottom 40th percentile of the metropolitan area were eligible to gentrify. Tracts were gentrified if residents ≥25 with a bachelor's degree increased and home price increased to the top third in the metropolitan area. Change in distribution of shootings and its relation to gentrification was our primary outcome while proximity of shootings to a trauma center was our secondary outcome. Results: Thirty-two percent (123/379) of eligible tracts gentrified and 31, 165 shootings were captured in the PPD database. 9090 (29.2%) patients meeting trauma criteria were captured in PTOS with an increasing proportion over time. The proportion of shootings within gentrifying tracts significantly dropped 2006–2018 (40%–35%, P < 0.001) and increased in non-gentrifying tracts (52%–57%, P < 0.001). In evaluation of shooting densities, a predictable redistribution occurred 2006–2018 with incident density decreasing in gentrified areas and increasing in non-gentrified areas. Shootings within 1 mile of a trauma center increased overall, but proportional access decreased in gentrified areas. Conclusions: Shootings in Philadelphia predictably moved out of gentrified areas and concentrated in non-gentrified ones. In this case study of a national crisis, the pattern of change paradoxically resulted in an increased clustering of shootings around trauma centers in non-gentrified areas. Repetition of this work in other cities can guide future resource allocation and be used to improve access to trauma care.